2017
DOI: 10.1097/ccm.0000000000002063
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Content of Fluids Used for Large-Volume Resuscitation Is Associated With Reduced Survival

Abstract: Objective We sought to investigate if the chloride content of fluids used in resuscitation was associated with short and long-term outcomes. Design We identified patients who received large volume fluid resuscitation (LVR), defined as greater than 60ml/kg over a 24 hour period. Chloride load was determined for each patient based on the chloride ion concentration of the fluids they received during LVR multiplied by the volume of fluids. We compared the development of hyperchloremic acidosis (HCA), AKI and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 36 publications
3
53
0
4
Order By: Relevance
“…At ISICEM 2016, Kellum presented results from a very large cohort of patients demonstrating that larger amounts of saline solution were associated with increased mortality compared to balanced solutions. These results were published as the current article was in press [34]. Contrary to widespread belief, the potassium content of balanced solutions does not cause hyperkalemia in renal insufficiency patients [35,36].…”
Section: Crystalloidsmentioning
confidence: 83%
“…At ISICEM 2016, Kellum presented results from a very large cohort of patients demonstrating that larger amounts of saline solution were associated with increased mortality compared to balanced solutions. These results were published as the current article was in press [34]. Contrary to widespread belief, the potassium content of balanced solutions does not cause hyperkalemia in renal insufficiency patients [35,36].…”
Section: Crystalloidsmentioning
confidence: 83%
“…32 Studies involving healthy volunteers suggest saline may decrease renal perfusion through chloride-mediated renal vaso-constriction. 33 Observational studies involving critically ill adults have shown higher rates of acute kidney injury, 34 renal-replacement therapy, 5,10 and death 6,7,9,35 with saline than with balanced crystalloids, although results have been inconsistent. 36 Although underpowered for clinical outcomes, two recent pilot trials involving critically ill adults showed an absolute difference of 1 percentage point in mortality in favor of balanced crystalloids.…”
Section: Discussionmentioning
confidence: 99%
“…1 Numerous publications have documented an association between administration of hyperchloraemic crystalloids (mostly normal saline) and various adverse outcomes, including increased incidence of renal replacement therapy, 7,8 AKI, 9 kidney graft dysfunction, 7 and mortality. 8,10,11 The overall evidence clearly provides a harm signal associated with hyperchloraemic crystalloid solutions without a comparable benefit signal, and supports the use of balanced instead of hyperchloraemic crystalloid solutions in most acute care patients. 12 The low chloride load associated with the administration of small volumes of normal saline may be well handled by patients at low risk for AKI.…”
Section: Declaration Of Interestmentioning
confidence: 69%